2013
DOI: 10.4155/fmc.12.197
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-Activated Prodrugs

Abstract: A prodrug is a compound that has negligible, or lower, activity against a specified pharmacological target than one of its major metabolites. Prodrugs can be used to improve drug delivery or pharmacokinetics, to decrease toxicity, or to target the drug to specific cells or tissues. Ester and phosphate hydrolysis are widely used in prodrug design because of their simplicity, but such approaches are relatively ineffective for targeting drugs to specific sites. The activation of prodrugs by the cytochrome P450 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 88 publications
(82 reference statements)
1
90
0
1
Order By: Relevance
“…i) The intra-CM-associated cytochrome P450 hydroxylation-activated (30,31) and intra-MM-associated cytochrome P450 hydroxylation-inactivated (31,32), sub-classified as a) The intra-CM-associated cytochrome P450 hydroxylation-activated DNA/RNA guanosine guanine alkylator procarbazine (33) (Log OWPC, -1.70; vdWD, 0.74 nm; Log OWPC-to-vdWD ratio, -2.29 nm -1 ); procarbazine hydrophilic moiety1 (Log OWPC, -0.59; vdWD, 0.51 nm; Log OWPC-to-vdWD ratio, -1.17 nm -1 ); procarbazine hydrophobic moiety1 (Log OWPC, 2.51; vdWD, 0.57 nm; Log OWPC-to-vdWD ratio, 4.43 nm -1 ); procarbazine hydrophilic moiety2 (Log OWPC, -1.11; vdWD, 0.43 nm; Log OWPC-to-vdWD ratio, -2.61 nm -1 ); procarbazine hydrophobic moiety2 (Log OWPC, 1.82; vdWD, 0.48 nm; Log OWPC-to-vdWD ratio, 3.75 nm -1 ): procarbazine alkylates DNA/RNA guanosine guanines via its CH 3 -NH 2 -NH 2 -terminal hydrophilic moiety1, but without the potential to crosslink (Table III and Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…i) The intra-CM-associated cytochrome P450 hydroxylation-activated (30,31) and intra-MM-associated cytochrome P450 hydroxylation-inactivated (31,32), sub-classified as a) The intra-CM-associated cytochrome P450 hydroxylation-activated DNA/RNA guanosine guanine alkylator procarbazine (33) (Log OWPC, -1.70; vdWD, 0.74 nm; Log OWPC-to-vdWD ratio, -2.29 nm -1 ); procarbazine hydrophilic moiety1 (Log OWPC, -0.59; vdWD, 0.51 nm; Log OWPC-to-vdWD ratio, -1.17 nm -1 ); procarbazine hydrophobic moiety1 (Log OWPC, 2.51; vdWD, 0.57 nm; Log OWPC-to-vdWD ratio, 4.43 nm -1 ); procarbazine hydrophilic moiety2 (Log OWPC, -1.11; vdWD, 0.43 nm; Log OWPC-to-vdWD ratio, -2.61 nm -1 ); procarbazine hydrophobic moiety2 (Log OWPC, 1.82; vdWD, 0.48 nm; Log OWPC-to-vdWD ratio, 3.75 nm -1 ): procarbazine alkylates DNA/RNA guanosine guanines via its CH 3 -NH 2 -NH 2 -terminal hydrophilic moiety1, but without the potential to crosslink (Table III and Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Presently, much of the knowledge about these enzymes is limited to their xenobiotic response, namely bioactivation of prodrugs and metabolic inactivation of drugs. Tamoxifen, cyclophosphamide, tegafur, and flutamide are some of the many anticancer agents that are administered as prodrugs [174]. Some reasons for designing chemotherapeutic agents as prodrugs include attenuating their cytotoxicity, preventing rapid degradation of their active metabolites, and achieving targeted delivery to the tumor site while sparing nontumor tissues [175,176].…”
Section: Relevance Of Cyp3a4 and Cyp3a5 To Drug Discoverymentioning
confidence: 99%
“…It has also been shown that these enzymes play an important role as an activating factor for oxazaphosphorine agents (Ortiz de Montellano 2013). Oxazaphosphorine is a class of anticancer drugs that includes cyclophosphamide (CPA) and ifosfamide (IFA).…”
Section: Enzyme/prodrug Systemsmentioning
confidence: 99%